Radiantguard umbrella / Ammar Faid Izzanol Bokiah ... [et al.] - Izzanol Bokiah, Ammar Faid; Abd Razak, Nur Elya Natasha; Abdullah Hedhir, Nur Ain; Abdul Kadir, Farah Aisyah; Mohd Ariff, Nur Shamimi Ayuni; Zulkefli, Zulfa Alwiyah (2023)
One of things in this world that we cannot control is the weather. Rain is an unexpected occurrence that used to happen in our daily lives without prior anticipation and prediction, catching people off guard and surprising them. This could lead to a sudden plan and activities as individuals may have not prepared for expected rain. Most people don't want to carry an umbrella, carrying an umbrella is inconvenient, especially if the person doesn't have a convenient place to store it when it's not to use, it can be cumbersome to carry an umbrella throughout the day, and people may not want to deal with the hassle. Therefore, our firm created an umbrella that can be seen in the dark, easy to store and an umbrella that is resistant to water. Our umbrella is not just an ordinary umbrella like you can find in any convenient store or online store that provides the basic function. Our umbrella is more than that, it solves all the problems in every aspect for those who use an umbrella. It is generally for protecting against rain but with additional technologies, such as umbrellas with Water-Repellent Coating. Our umbrellas come with special coatings that make them resistant to water. This coating helps rainwater bead up and roll off the surface of the umbrella rather than being absorbed. Our material that we used in the umbrella helps it to dry itself without even having to wait. It can avoid the musty odor even after we store it in a closed environment. In terms of convenience, our umbrella is specially made for easy to carry and store while not using it. We also added a glow in the dark feature to our umbrella, the glowing feature makes you more visible to others during nighttime or in a situation with reduced lighting, enhancing when walking.